The Value of Population Screening in Advancing Personalized Medicine in the Field of Lung Cancer - Mogenet A; Greillier L; Tomasini P (Dove Medical Press, 2021)
Alice Mogenet, Laurent Greillier, Pascale Tomasini Aix Marseille University, CNRS, INSERM, CRCM, APHM, Multidisciplinary Oncology & Therapeutic Innovations Department, Marseille, FranceCorrespondence: Pascale TomasiniService d'Oncologie Multidisciplinaire et Innovations Thérapeutiques, Hôpital Nord, Chemin des Bourrely, Marseille Cedex, 13915, FranceTel +33 4 91 96 59 01Fax +33 4 91 96 59 02Email pascale.tomasini@ap-hm.frAbstract: During the past decade, progress has been made in the field of lung cancer molecular biology and onco-immunology, leading to prolonged survival of patients. The combination of increased fundamental knowledge and the pharmaceutical pipeline has allowed the development of various tyrosine kinase inhibitors, targeting numerous molecular alterations. These drugs are now available in daily practice and have transformed survival outcomes for patients harboring EGFR, ALK or ROS1 alterations. Multiple clinical trials are now ongoing in order to increase the number of approved drugs, thus overcoming the issues of rare mutations and tyrosine kinase inhibitors resistance. Immune checkpoint inhibitors development has also changed lung cancer outcomes, but underwhelming response rates highlight the need for immune biomarkers. While PD-L1 expression was the first approved immune biomarker, it has shown several limitations and new biomarkers have to be identified to predict response or resistance to immune checkpoint inhibitors. Testing methods, molecular results and targeted therapeutic schedules will be harmonized in the coming years, with the help of dedicated molecular multidisciplinary boards.Keywords: molecular biology, targeted therapy, lung cancer, immunotherapy, biomarkers